2013
DOI: 10.6061/clinics/2013(12)05
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of multiple thrombogenic and atherogenic markers in premature coronary artery disease

Abstract: OBJECTIVE:To examine the association of atherogenic and thrombogenic markers and lymphotoxin-alfa gene mutations with the risk of premature coronary disease.METHODS:This cross-sectional, case-control, age-adjusted study was conducted in 336 patients with premature coronary disease (<50 years old) and 189 healthy controls. The control subjects had normal clinical, resting, and exercise stress electrocardiographic assessments. The coronary disease group patients had either angiographically documented disease (>5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The nutritional value and disease preventive potential of a vegetable oil is evaluated based on three factors: atherogenic index (AI), thrombogenic index (TI), hypocholesterolemic: hypercholesterolemic ratio (HH), polyunsaturated fatty acids: saturated fatty acids ratio (PUFA:SFA) and the ω6:ω3 ratio. All these factors are influenced by the composition of FAs in the oils (Hashempour‐Baltork et al, 2018; Mansur et al, 2013).…”
Section: Blending: Need and Benefitsmentioning
confidence: 99%
“…The nutritional value and disease preventive potential of a vegetable oil is evaluated based on three factors: atherogenic index (AI), thrombogenic index (TI), hypocholesterolemic: hypercholesterolemic ratio (HH), polyunsaturated fatty acids: saturated fatty acids ratio (PUFA:SFA) and the ω6:ω3 ratio. All these factors are influenced by the composition of FAs in the oils (Hashempour‐Baltork et al, 2018; Mansur et al, 2013).…”
Section: Blending: Need and Benefitsmentioning
confidence: 99%
“…The electronic database search identified 348 studies. After the screening, a total of 11 studies [6,[22][23][24][25][26][27][28][29][30][31] met the inclusion criteria. Individual study characteristics are presented in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…[28] and Mansur et al . [25] after introducing lipoprotein(a) as a dichotomous variable (lipoprotein(a) >20 mg/dl or >30 mg/dl) and adjusting for lipid profile and/ or cardiovascular risk factors, found that elevated lipoprotein(a) levels are associated with increased odds of pCAD development. Rallidis et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process presented 117 potential eligible articles. Then, the final screening process was performed using the inclusion/exclusion criteria (the Outcome and Comparison) which included 17 articles into the present systematic review and meta-analysis [17][18][19][20][21][27][28][29][30][31][32][33][34][35][36][37][38] (Figure 1). The full-text of one article was not found after two reminders to the authors and the publishing journal.…”
Section: Study Characteristicsmentioning
confidence: 99%